2010
DOI: 10.1155/2010/821531
|View full text |Cite
|
Sign up to set email alerts
|

A New Subclass of Salagean‐Type Harmonic Univalent Functions

Abstract: We define and investigate a new subclass of Salagean-type harmonic univalent functions. We obtain coefficient conditions, extreme points, distortion bounds, convolution, and convex combination for the above subclass of harmonic functions.which are analytic in the open unit disk Í {z ∈ : |z| < 1}.We denote the subclass of A consisting of analytic and univalent functions f z in the unit disk Í by S.The following classes of functions and many others are well known and have been studied repeatedly by many authors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Note that this problem has yet to be solved for certain classes introduced in various studies (see for examples [5], [21], [22] and [23]). Note that Hankel problems have also been solved successfully for fractional operator which can be seen in [20].…”
Section: Resultsmentioning
confidence: 99%
“…Note that this problem has yet to be solved for certain classes introduced in various studies (see for examples [5], [21], [22] and [23]). Note that Hankel problems have also been solved successfully for fractional operator which can be seen in [20].…”
Section: Resultsmentioning
confidence: 99%
“…α β λ ′ ′ + Note: Some other study can also be found in the articles written by (Al-Shaqsi et al, 2010). Most of the results may look similar, but they do have plentiful applications in area of studies.…”
mentioning
confidence: 80%
“…Note that this problem has yet to be solved for certain classes introduced in various studies (see for examples [5], [21], [22] and [23]). Note that Hankel problems have also been solved successfully for fractional operator which can be seen in [20].…”
Section: Ma'moun Harayzeh Al-abbadi and Maslina Darusmentioning
confidence: 99%